The Emergence of National Interest: The Impactful Trigger for Arab Israeli Normalization - Syahri Helmi Zacky; Abdul Muta'ali (Universitas Muhammadiyah Gorontalo, 2022)
The normalization of relations between the United Arab Emirates and Israel from August to September 2020 marked a new chapter in Middle East geopolitical dynamics. Although this normalization began with hopes of Israeli-Palestinian peace through the Abraham Accords, the reality has been quite the opposite. Israeli violence against Palestinians and the construction of illegal settlements continue, sparking condemnation and rejection from various parties, including Muslims and Palestinian supporters.This research is motivated by the normalization agreement of four Arab countries with Israel in a short time span. The reason is the four Arab countries understand that this normalization agreement will receive bad perspective regarding their contribution to the struggle for Palestinian independence. Sources of data in this study came from national and international journals, as well as report data from national and international news media related to this topic. The research method used in this study is qualitative method with geopolitical approach. The theory used by the researcher is the paradigm of political realism proposed by Morgenthau and the existential theory proposed by Samuel P. Huntington. This article concludes that the motivation of Arab countries in carrying out normalization is the national interest of each country and the stability of the country and region.